2021
DOI: 10.1158/1535-7163.mct-20-0002
|View full text |Cite
|
Sign up to set email alerts
|

AZD0364 Is a Potent and Selective ERK1/2 Inhibitor That Enhances Antitumor Activity inKRAS-Mutant Tumor Models when Combined with the MEK Inhibitor, Selumetinib

Abstract: The RAS-regulated RAF-MEK1/2-ERK1/2 (RAS/MAPK) signalling pathway is a major driver in oncogenesis and is frequently dysregulated in human cancers, primarily by mutations in BRAF or RAS genes. The clinical benefit of inhibitors of this pathway as single agents has only been realized in BRAF mutant melanoma, with limited effect of single agent pathway inhibitors in KRAS mutant tumours. Combined inhibition of multiple nodes within this pathway, such as MEK1/2 and ERK1/2, may be necessary to effectively suppress … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 39 publications
5
20
1
Order By: Relevance
“…The RAS-RAF-MEK1/2-ERK1/2 (RAS/MAPK) signalling pathway is frequently dysregulated in human cancers, often by mutations in BRAF or RAS genes and therefore is an important node for development of novel oncology compounds. In a recent publication, the ERK 1/2 inhibitor AZD0364 was profiled across different in vivo xenograft models [ 23 25 ]. Treatment of the non-small cell lung cancer (NSCLC) Calu-6 KRAS mutant xenograft model with AZD0364 at 50 mg/kg once daily (QD) for 21 days resulted in tumour regressions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The RAS-RAF-MEK1/2-ERK1/2 (RAS/MAPK) signalling pathway is frequently dysregulated in human cancers, often by mutations in BRAF or RAS genes and therefore is an important node for development of novel oncology compounds. In a recent publication, the ERK 1/2 inhibitor AZD0364 was profiled across different in vivo xenograft models [ 23 25 ]. Treatment of the non-small cell lung cancer (NSCLC) Calu-6 KRAS mutant xenograft model with AZD0364 at 50 mg/kg once daily (QD) for 21 days resulted in tumour regressions.…”
Section: Resultsmentioning
confidence: 99%
“…Treatment of the non-small cell lung cancer (NSCLC) Calu-6 KRAS mutant xenograft model with AZD0364 at 50 mg/kg once daily (QD) for 21 days resulted in tumour regressions. In comparison, the A549 NSCLC KRAS mutant xenograft model was less sensitive to the same dose of AZD0364 reaching only partial tumour growth inhibition (TGI) [ 23 ]. The purpose of this experiment was to use the Microformulator to determine if this difference in response of the 2 KRAS mutant xenografts to AZD0364 could be replicated in an in vitro system and, if so, to compare results to traditional fixed concentration bolus dosing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical studies are ongoing to examine its role in tumors harboring activating MAPK mutations as a single agent or in combination with other agents (NCT03698994, NCT04145297). Recently, the combination of AZD0364, a selective Erk1/2 inhibitor, and selumetinib has been shown to alleviate tumor progression in multiple xenograft models of KRAS-mutant NSCLC [139]. Similarly, Catalano et al showed that dual inhibition of MEK and Erk represented anti-tumor efficacy and blocked the emergence of drug resistance in an HRAS G12C -driven autochthonous sarcoma model.…”
Section: Erk Inhibitorsmentioning
confidence: 99%
“…A novel molecule selectively targeting ERK, SCH772984, induced tumor regression in mouse xenograft models with KRAS or NRAS mutations [154]. AZD0364 exhibited dose-and time-dependent modulation of ERK1/2-dependent signaling to result in tumor regression in sensitive BRAFand KRAS-mutant xenografts [157,158]. Another similar small molecule, BVD523 (ulixertinib), exhibited antitumor activity for MEK-BRAF in concurrent or single targeting in resistant models in vitro or in vivo [156].…”
Section: Erk Inhibitionmentioning
confidence: 99%